Stress Tests for Defined Benefit Pension Plans : A Primer - Impavido, Gregorio (IMF Working Papers; Working Paper ;, 2011)
Stress testing is a useful and increasingly popular, yet sometimes misunderstood, method of analyzing the resilience of financial systems to adverse events. This paper aims to help demystify stress tests and illustrate their strengths and weaknesses. Using an Excel-based template with institution-specific data, readers are walked through the basics of liability valuation and stress testing of assets and liabilities of a typical defined benefit plan.